Influence of geomechanics parameters on stress sensitivity in fractured reservoir - Feng, Yutian; Tang, Hongming; Tang, Haoxuan; Leng, Yijiang; Shi, Xuewen; Liu, Jia; Wang, Zhao; Deng, Cong (Frontiers in Earth Science, 2023)
The complex fractures aggravate stress sensitivity and heterogeneity of the reservoir and seriously restrict effective development. Therefore, it is of great significance to study and quantitatively evaluate the stress sensitivity of the fractured reservoir. Taking the typical block of the Longmaxi shale reservoir in southern Sichuan as the engineering background, one uses the finite element method to develop a numerical model of a two-dimensional fracture closure variation subjected to the non-hydrostatic stress field. It explores the influence of different fracture occurrences and rock mechanical parameters on stress sensitivity. The theoretical model verifies the numerical simulation results to reveal the stress sensitivity mechanism of the fractured reservoir. The results show that the influence of the dip angle of fracture on the stress sensitivity depends on the anisotropy of applied in-situ stresses. The stronger stress sensitivity occurs in low-dip angles where the lateral pressure coefficient is less than 1. One defines the lateral pressure coefficient. On the contrary, the stronger stress sensitivity occurs in high-dip angles where the lateral pressure coefficient is more significant than 1. It is because the normal stress differences under different stress fields apply to the fracture. Under a given stress condition, the stress sensitivity of fracture negatively correlates with aspect ratio, elastic modulus, and Poisson’s ratio. Pressure maintenance may be more critical in a reservoir with a low aspect ratio and rich in soft minerals. The theoretical predicting model of fracture permeability under different conditions is established based on the linear elastic theory. The relative error between theoretically predicted results and numerical simulation ones is less than 10%, which verifies the accuracy of numerical simulation results. The fundamental reason for stress sensitivity in the fractured reservoir is the fracture geometry and mineral deformation change. The research results are of great significance for establishing the productivity equation considering the stress sensitivity, accurately evaluating the variation of reservoir seepage capacity, and formulating reasonable drainage and production system.